A Novel Approch For Development And Charectrization Of Etoposide Loaded Solid Lipid Nanoparticles - SOMPUR C.K.; DOIJAD R.C.; GOJE ARJUN (International Journal of Pharma and Bio Sciences, 2011)
In recent years Solid Lipid Nanoparticles are regarded as alternative carrier systems to traditional colloidal systems. Drug loaded of twelve batches of different ratios of SLNs were prepared by solvent displacement method. Differing theoretical loading of ET 10, 20, 30 and 40% w/w of polymers respectively. The obtained ETSLN nanoparticles formulations ET1, ET2, ET3, ET4, ET5,ET6, ET7, ET8, ET9, ET10, ET11 and ET12 were evaluated for percentage yield, drug loading, percentage entrapment efficiency, particle size, surface morphology, in vitro release rate studies. ET4 shows maximum percentage yield of 84.73%, entrapment efficiency of 19.80±0.35 and particle size of 0.198±0.031. ETSLN were superficially spherical in shape with smooth surface and shows sustained release pattern for up to 90 hrs.